High-resolution X-ray absorption spectroscopy of alkanethiolate self-assembled monolayers on Au(111) and Ag(111) - Feulner, Peter; Zharnikov, Michael (Journal of electron spectroscopy and related phenomena, 2021)
High-resolution C K-edge near-edge X-ray absorption fine structure (NEXAFS) spectra of non-substituted alkanethiolate self-assembled monolayers (SAMs) on Au(111) and Ag(111) were studied, with a particular emphasis on their fine structure and temperature dependence. Depending on the orientation of the light polarization with respect to the surface normal, the spectra were either dominated by the 'C−H' band, comprised of several σ*C−H / Rydberg resonances or exhibited several usually "hidden" features, including a sharp pre-edge resonance at ∼286.8 eV, related to the terminal methyl group of the SAM forming molecules and accompanied by a vibronic feature. The spectra exhibit pronounced reversible temperature dependence at going from cryogenic (60−70 K) to room temperature, including a shift of the 'C−H' band to lower energy by 250−300 meV, broadening and decrease in intensity of nearly all resonances, and disappearance of several "fine structure" features. This behavior was attributed to the nuclear motion effects, with the major impact of progressing orientational and conformational disorder in the SAMs, and correlated with the length of the of molecular backbone and specific character of the SAM-ambient interface.
Gesehen am 20.05.2021